1998
DOI: 10.1002/(sici)1099-1271(199803/04)13:2<75::aid-bio469>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenol derivatives as enhancers and inhibitors of luminol-H2O2-horseradish peroxidase chemiluminescence

Abstract: Systematic studies on phenol derivatives facilitates an explanation of the enhancement or inhibition of the luminol-H2O2-horseradish peroxidase system chemiluminescence. Factors that govern the enhancement are the one-electron reduction potentials of the phenoxy radicals (PhO./PhOH) vs. luminol radicals (L./LH-) and the reaction rates of the phenol derivatives with the compounds of horseradish peroxidase (HRP-I and HRP-II). Only compounds with radicals with a similar or greater reduction potential than luminol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…A model compound with an orthosubstituted hydroxyl group to the aromatic ring seems to be adequate for the antioxidant and H 2 O 2 -or DPPH-scavenging activity of phenolic acids [61]. The phenolic compounds act as effective donors or oxygen acceptors in the presence of H 2 O 2 [62,63]. It has been reported that compounds with a hydroxyl group in the ortho position of the phenolic ring have peroxyl radical-and superoxide-scavenging properties [64].…”
Section: Discussionmentioning
confidence: 99%
“…A model compound with an orthosubstituted hydroxyl group to the aromatic ring seems to be adequate for the antioxidant and H 2 O 2 -or DPPH-scavenging activity of phenolic acids [61]. The phenolic compounds act as effective donors or oxygen acceptors in the presence of H 2 O 2 [62,63]. It has been reported that compounds with a hydroxyl group in the ortho position of the phenolic ring have peroxyl radical-and superoxide-scavenging properties [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the scavenging activity of formaldehyde, which is used clinically in root canal treatment, as are the phenolic compounds, was much lower than those of the phenolic compounds. It seems likely that the difference of radical scavenging activity is due to the difference between the aromatic and the aldehydic features of these compounds, i.e., due to the fact that the phenolic compounds, but not formaldehyde, act as effective electron donors and oxygen acceptors in the presence of H 2 O 2 (1,18 (18). It seems reasonable that guaiacol acts as an inhibitor of luminol chemiluminescence, because the Hammett constant of guaiacol is approximately − 0.27 (18).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the difference of radical scavenging activity is due to the difference between the aromatic and the aldehydic features of these compounds, i.e., due to the fact that the phenolic compounds, but not formaldehyde, act as effective electron donors and oxygen acceptors in the presence of H 2 O 2 (1,18 (18). It seems reasonable that guaiacol acts as an inhibitor of luminol chemiluminescence, because the Hammett constant of guaiacol is approximately − 0.27 (18). The present results thus strongly demonstrate that the • OH scavenging activity of phenolic compounds, especially guaiacol, was in fact due to their radical scavenging properties, and not to metal-chelating capacity or a direct reaction with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of piodophenol, the phenoxy radical is thought to play an important role in the enhancing effect. 22,23 The decrease in the enhancing effect of p-iodophenylboronic acid or 4-biphenylboronic acid in the presence of saccharides was attributed to the interaction between the diol group of the saccharide and the boronic acid moiety of the enhancer. The interaction eliminated the possibility of generating such radicals.…”
Section: -Ch(oh)-ch(ch2oh)-mentioning
confidence: 99%